Relational, communicational and synergistic function of Public Relations in public and private organizations in Peru - Valdez Orriaga, Miguel (2015)
This investigation led proposes the articulation, in a conception as a whole, of a new theoretical model based on the stablishment of three functions of Public Relations that should be present in public and private organizations, that are, the relational function, the communicational function and the synergy function. This is an exploratory study, non-experimental, descriptive, comparative, and from an intracultural mode that took a sample of twenty executive officers of Public Relations and related, from public and private organizations in Peru. Among the main results it was found a high level of management in human relations in private organizations in Lima, but a low level in other cities of the country. These high and low levels were found in the management of the public controversy in organizations of Lima and provinces, respectively. Likewise, a high level of the subfunction unidirectional oversized message was found in private organizations in Lima, and rather low in provinces.